Molecular dynamics simulation on devitrification: Isothermal devitrification and thermodynamics of PbF2 glasses - Silva, MAP; Rino, J. P.; Monteil, A.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2004)
The vitrification and devitrification features of lead fluoride are investigated by means of molecular dynamic simulations. The influence of heating rate on the devitrification temperature as well as the dependence of the glass properties on its thermal history, i.e., the cooling rate employed, is identified. As expected, different glasses are obtained when the cooling rates differ. Diffusion coefficient analysis during heating of glass and crystal, indicates that the presence of defects on the glassy matrix favors the transition processes from the ionic to a superionic state, with high mobility of fluorine atoms, responsible for the high anionic conduction of lead fluoride. Nonisothermal and isothermal devitrification processes are simulated in glasses obtained at different cooling rates and structural organizations occurring during the heat treatments are clearly observed. When a fast cooling rate is employed during the glass formation, the devitrification of a single crystal (limited by the cell dimensions) is observed, while the glass obtained with slower cooling rate, allowing relaxations and organization of various regions on the glass bulk during the cooling process, devitrifies in more than one crystalline plane. (C) 2004 American Institute of Physics.